Analisis Struktural Puisi “Tiada” Karya Joko Pinurbo - Silva Caesarani Destiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Poetry is one type of literary work in which there are a series of words that contain meaning. Therefore, to understand more deeply about the poem requires an in-depth study. The purpose of this study is to describe the structure of the poem where there are physical elements and mental elements in the poem